2017
DOI: 10.14715/cmb/2017.63.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of insulin receptor substrate (IRS) proteins in oncogenic transformation

Abstract: Insulin Receptor Substrate (IRS) proteins are the main cytoplasmic adaptor molecules involved in transducing extracellular signals from receptors to downstream proteins. This protein family have pivotal roles on maintenance, distribution and regulation of signaling networks. Since IRS1/2 interact with and transmits signals from the receptors of insulin, Insulin Like Growth Factor 1 (IGF1), prolactin, growth hormone (GH), leptin, Vascular Endothelial Growth Factor (VEGF), TrkB, ALK and integrins this promoted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…Mechanistically, this study identified IRS1 could be directly targeted by miR-126 for downregulation. The reduction of IRS1 was observed both in mRNA and protein levels, suggesting the ability of miR-126 in degradating IRS1 mRNA.IRS1 functions as a key molecule that transmits signals from IGF-1R to downstream pathways such as the PI3K/Akt and MAPK pathways [17]. Overexpression of IRS1 was reported to promote the proliferation of hepatocytes and thus potentially contributed to HCC progression [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, this study identified IRS1 could be directly targeted by miR-126 for downregulation. The reduction of IRS1 was observed both in mRNA and protein levels, suggesting the ability of miR-126 in degradating IRS1 mRNA.IRS1 functions as a key molecule that transmits signals from IGF-1R to downstream pathways such as the PI3K/Akt and MAPK pathways [17]. Overexpression of IRS1 was reported to promote the proliferation of hepatocytes and thus potentially contributed to HCC progression [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression levels of IGF-1R and IRS1 are associated with many human malignancies which implies that both of the proteins have a pivotal role in carcinogenesis (9,21,22). Recent studies have also shown that IGF-1R and IRS1 are responsible for the development of chemo-and radioresistance in cancer cells but their molecular mechanisms have not been discovered yet (23).…”
Section: Discussionmentioning
confidence: 99%
“…Its expression is induced by many oncogenes such as MAPK and AKT during carcinogenesis and hypoxia (31). During insulin signaling, glucose uptake rates of the cells is regulated by IRS1 proteins through the activation of AKT and translocation of GLUT proteins to the cell membrane (9). GLUT1 expression could be elevated by increased IRS1 expression in A172 cells and this overexpression may cause to reduce the sensitivity to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When IRS1 binds to its receptors, it is phosphorylated on tyrosine residues. Tyrosine phosphorylation of IRS1 induces the activation of PI3K-AKT and Ras-ERK pathways [13]. Transformation capacity of IRS1 was first shown in mouse embryonic fibroblasts and its overexpression is primarily responsible for cell proliferation in breast cancer [4].…”
Section: Introductionmentioning
confidence: 99%